Chipless RFID tag mounted on a conformal platform - Zhong, Cheng (Nanyang Technological University, 2022)
Most of the existing radio frequency identification (RFID) tag use micro-chips that store the identification information. They are widely used in Internet of Things (IOT) to achieve the connection between things and people. RFID tag is the main part of RFID system, but the cost of tag production is usually high and not commercial to use. There is an interest in chipless RFID tags that do not require micro-chips as the RFID antenna bears the identification information. In order to extend the applications of such chipless RFID tags, this dissertation aims to develop several chipless RFID tags that can be mounted on conformal platforms. A “C” like chipless RFID tag is designed, which can be attached to a metal conformal platform in practical applications. Simulations using ANSYS high frequency structure simulator (HFSS) will be conducted to verify the designed chipless RFID tags.